Preferential localization of human origins of DNA replication at the 5'-ends of expressed genes and at evolutionarily conserved DNA sequences. - Manuel S Valenzuela; Yidong Chen; Sean Davis; Fan Yang; Robert L Walker; Sven Bilke; John Lueders; Melvenia M Martin; Mirit I Aladjem; Pierre P Massion; Paul S Meltzer (PLoS ONE)
Background Replication of mammalian genomes requires the activation of thousands of origins which are both spatially and temporally regulated by as yet unknown mechanisms. At the most fundamental level, our knowledge about the distribution pattern of origins in each of the chromosomes, among different cell types, and whether the physiological state of the cells alters this distribution is at present very limited. Methodology/principal findings We have used standard λ-exonuclease resistant nascent DNA preparations in the size range of 0.7-1.5 kb obtained from the breast cancer cell line MCF-7 hybridized to a custom tiling array containing 50-60 nt probes evenly distributed among genic and non-genic regions covering about 1% of the human genome. A similar DNA preparation was used for high-throughput DNA sequencing. Array experiments were also performed with DNA obtained from BT-474 and H520 cell lines. By determining the sites showing nascent DNA enrichment, we have localized several thousand origins of DNA replication. Our major findings are: (a) both array and DNA sequencing assay methods produced essentially the same origin distribution profile; (b) origin distribution is largely conserved (>70%) in all cell lines tested; (c) origins are enriched at the 5'ends of expressed genes and at evolutionarily conserved intergenic sequences; and (d) ChIP on chip experiments in MCF-7 showed an enrichment of H3K4Me3 and RNA Polymerase II chromatin binding sites at origins of DNA replication. Conclusions/significance Our results suggest that the program for origin activation is largely conserved among different cell types. Also, our work supports recent studies connecting transcription initiation with replication, and in addition suggests that evolutionarily conserved intergenic sequences have the potential to participate in origin selection. Overall, our observations suggest that replication origin selection is a stochastic process significantly dependent upon local accessibility to replication factors.